FRI0453 Hospitalisation and survival analysis in systemic sclerosis patients with concomitant or isolated pulmonary hypertension and interstitial lung disease in the multiethnic scleroderma cohort singapore. (12th June 2018) - Noviani, M.; Seyed, E.S.; Kua, S.M.Y.; Chan, G.Y.L.; Teng, G.G.; Law, W.G.; Santosa, A.; Lim, A.; Tan, J.L.; Tay, E.L.W.; Yip, J.W.L.; Ng, S.C.; et al.
Abstract : Background: Concomitant pulmonary hypertension and interstitial lung disease in systemic sclerosis (SSc-PH-ILD) represents a distinct subpopulation of SSc with poorer prognosis in Western studies. In Asian patients, characterisation of SSc-PH-ILD is still lacking. Objectives: To analyse hospital admissions, survival and prognostic markers among SSc patients with PH, ILD or concomitant PH-ILD in the S cleroderma C ohort Singapore . Methods: In this study involving 3 tertiary Rheumatology institutions Jan 2008 to, Oct 2016 SSc patients with significant pulmonary involvement were included. ILD was based on high resolution computed tomography and predicted FVC <70%. PH was based on either echocardiographic systolic pulmonary arterial pressure (sPAP) ≥50 mmHg, or right heart catheterization (RHC) findings of mean PAP≥25 mmHg. Hospitalisation rates and survival of SSc patients with PH, ILD or PH-ILD were compared. Risk factors of poor outcomes were identified by multivariate stepwise Cox regression analysis. Results: Among 490 patients, 92 had ILD, 50 PH and 43 PH-ILD (table 1). Of 93 patients with PH or PH-ILD, 56 were based on echocardiography and 37 on RHC. The 5 year survival was 79%, 87% and 90% in PH, PH-ILD and ILD subgroup, respectively (figure 1). In multivariable analysis, PH was significantly associated with 2.8-fold increased risk of death. Male gender, malabsorption, digital ulcerations and renal crisis were also significantly associated with mortality (table 2). No significant difference in hospital admissions/year among different subgroups. Increased hospital admissions were associated with renal crisis, right heart failure and use of PH medications. Conclusions: Compared to those with ILD or PH-ILD, SSc-PH patients had increased mortality, but not hospitalisation rates. This could be due to small sample size or short follow up duration. We identified risk factors associated with worse outcomes in SSc patients with significant pulmonary involvement. Disclosure of Interest: None declared